2021
DOI: 10.33448/rsd-v10i15.22440
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvendo vídeos para proporcionar acessibilidade aos visitantes surdos nos centros de ciências itinerantes

Abstract: A acessibilidade para os surdos nos espaços de divulgação científica é um direito garantido por lei, mas pouco implementado. Esta pesquisa participativa de abordagem qualitativa teve por objetivo apresentar o processo de desenvolvimento de vídeos guias para centros de ciências itinerantes e as estratégias utilizadas para sanar os problemas identificados, bem como analisar a opinião dos surdos sobre o material desenvolvido. Para isso, produzimos vídeos guias em Libras e os apresentamos para um grupo de 30 surdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 6 publications
0
5
0
6
Order By: Relevance
“…In CST's videos in BSL, we decided to use more classifiers and imagery descriptions as well as inserting illustrative images. In addition, the videos had subtitles at the bottom, and whenever a term was spelled (fingerspelling -writing words with a manual alphabet), it was displayed with the capital letters in the subtitles (Ferreira, 2021a). These strategies had three goals: (a) to help the understanding of fingerspelling and some signs that may not be known by the deaf visitor, either because there is a linguistic variation or because they have never seen that signal before, especially scientific terms; (b) to diversify the way content is presented, as it is not possible to affirm that all deaf people have the same difficulty with written Portuguese or that all of them have fluency of sign language-some deaf people may find reading/writing as the best way for learning while others may better understand through images; and (c) to serve a larger audience since some deaf people do not use sign language and communicate orally using, preferably, lip reading, writing, and oralization to communicate (Perlin, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In CST's videos in BSL, we decided to use more classifiers and imagery descriptions as well as inserting illustrative images. In addition, the videos had subtitles at the bottom, and whenever a term was spelled (fingerspelling -writing words with a manual alphabet), it was displayed with the capital letters in the subtitles (Ferreira, 2021a). These strategies had three goals: (a) to help the understanding of fingerspelling and some signs that may not be known by the deaf visitor, either because there is a linguistic variation or because they have never seen that signal before, especially scientific terms; (b) to diversify the way content is presented, as it is not possible to affirm that all deaf people have the same difficulty with written Portuguese or that all of them have fluency of sign language-some deaf people may find reading/writing as the best way for learning while others may better understand through images; and (c) to serve a larger audience since some deaf people do not use sign language and communicate orally using, preferably, lip reading, writing, and oralization to communicate (Perlin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This could be one of the reasons why, during the validation process, the group had more difficulty in understanding compared to our student participants of the research. During the validation process, the videos were watched in isolation without the practical activity (Ferreira, 2021a), while, at the research stage, the videos were watched during an in-person visit along with the interactive activity. found that there is an active construction of knowledge when individuals handle and explore a studied object, which could explain why active methodologies are easier to understand.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations